2024
DOI: 10.1073/pnas.2313677121
|View full text |Cite
|
Sign up to set email alerts
|

Structure of saguaro cactus virus 3′ translational enhancer mimics 5′ cap for eIF4E binding

Manju Ojha,
Jeff Vogt,
Naba Krishna Das
et al.

Abstract: The genomes of several plant viruses contain RNA structures at their 3′ ends called cap-independent translation enhancers (CITEs) that bind the host protein factors such as mRNA 5′ cap-binding protein eIF4E for promoting cap-independent genome translation. However, the structural basis of such 5′ cap-binding protein recognition by the uncapped RNA remains largely unknown. Here, we have determined the crystal structure of a 3′ CITE, panicum mosaic virus-like translation enhancer (PTE) from the saguaro cactus vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Crystal structures have shown that a guanosine is extruded from a G-rich stretch in the PTE of the pea-enation mosaic virus (PEMV2), providing a structural basis for eIF4E recognition [ 207 ]. Similar studies in the saguaro cactus virus (SCV) revealed a flipped-out G residue ready to dock into the 5′ cap-binding pocket of eIF4E, highlighting 5′ cap mimicry by a 3′-CITE [ 208 ]. 3′-CITEs in T-shaped structures (TSSs) in TCV and cardamine chlorotic fleck virus RNAs can recycle post-termination ribosomes or ribosomal subunits directly to the 5′-end [ 209 , 210 ].…”
Section: 3′ End Elementsmentioning
confidence: 99%
“…Crystal structures have shown that a guanosine is extruded from a G-rich stretch in the PTE of the pea-enation mosaic virus (PEMV2), providing a structural basis for eIF4E recognition [ 207 ]. Similar studies in the saguaro cactus virus (SCV) revealed a flipped-out G residue ready to dock into the 5′ cap-binding pocket of eIF4E, highlighting 5′ cap mimicry by a 3′-CITE [ 208 ]. 3′-CITEs in T-shaped structures (TSSs) in TCV and cardamine chlorotic fleck virus RNAs can recycle post-termination ribosomes or ribosomal subunits directly to the 5′-end [ 209 , 210 ].…”
Section: 3′ End Elementsmentioning
confidence: 99%